MODERN FEATURES OF CHICKEN POX COURSE IN ADULTS - Volobuieva, Olha; Liadova, Tetiana; Sevastianova, Tetiana; Volobuiev, Daniil (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2019)
The article presents the epidemiological and clinical data of the modern course of chickenpox. A high incidence among adults with a bright manifestation of the clinical picture was shown. Recurrent episodes of chicken pox were marked. The modern course of varicella in Ukraine is characterized by an increase in the incidence among the adult population. Infection is manifested by a long prodromal period, a pronounced intoxication syndrome, lymphadenopathy, and an abundant polymorphic rash. At the same time, the rash had a pustular character in 54.3 % of patients; exanthema was observed with scleritis and conjunctivitis in 45 % of cases. There are repeated cases of chickenpox, the interval between these episodes ranged from 5 to 12 years. Taking into account the epidemiological situation in the country it remains relevant to study main features of the course of chickenpox in individuals against the background of pulmonary tuberculosis, depending on the age and duration of the underlying disease.